Strategic Planning Based on the Impact of Social Support and Social Trust on COVID-19 Risk Response in Formal and Informal Workers - Nisa Aprilia, Karina; Muslim, Erlinda (Jurnal Sistem Teknik Industri, 2023)
The COVID-19 pandemic has occurred throughout the world, and also in Indonesia. The government try to reduce the spread of COVID-19 by implementing various policies such as the large-scale social restriction (PSBB) policy, as well as other related policies. However, this policy has not been effective in view of the level of the spread of COVID-19 which has not decreased. Lack of public awareness is the cause of the spread of COVID-19 in Indonesia. For this reason, this study examines the effect of social support and social trust on the efficacy response to COVID-19 using the structural equation modeling (SEM) method. This factor was chosen because social support is an important aspect of the life of Indonesian society. This research was conducted on formal and informal workers, because workers are still required to have activities outside the home. The results show that social support and social trust are more influential on formal workers than informal workers. Strategy recommendations are compiled based on literature studies. After that, the weighting was done by using a relationship matrix. The results of the relationship matrix are seven prioritized strategies for formal workers, and three prioritized strategies for informal workers.